Proceso administrativo y su incidencia en la efectividad de las actividades docentes de la Unidad Educativa Oswaldo Villamil Auz del cantón Quevedo - Velasco Tuarez, María Enriqueta (2017)
With the present research work is intended to highlight the relevance of the implementation of an action plan to train teachers of the Educational Unit "Oswaldo Villamil Auz" Canton Quevedo year 2017, as this will serve as a great help to solve the problems that this institution is presenting, through seminars where the knowledge of the teachers is strengthened and strengthened and in this way provide a quality education. The population surveyed in the present investigation is made up of 34 participants who are subdivided into 24 teachers, 8 administrative and 2 authorities, because it is a small population, no sampling will be applied and the total population will be worked on. To carry out this research study the use of the following methods and very important research techniques were used: Direct observation, questionnaire, survey and interview which were directed to the aforementioned population In order to achieve this research, the general objective was to: Determine the incidence of the administrative process on the effectiveness of the teaching activities of the "Oswaldo Villamil Auz" Educational Unit in Cantón Quevedo, 2017; and specific objectives: Determine the relationship of the planning process in the effectiveness of the teaching activities of the Educational Unit "Oswaldo Villamil Auz" Quevedo year 2017; Analyze the process of organization and its relation with the effectiveness of the educational activities of the Educational Unit "Oswaldo Villamil Auz" Quevedo year 2017; Determine the relationship of the management process in the effectiveness of the teaching activities of the Educational Unit "Oswaldo Villamil Auz" Quevedo. In order to achieve these objectives, information was gathered from various sources describing the administrative processes and the role or activities that teachers must perform.